Learning Transformation in the Post-Pandemic Era: Synergy of Teacher and Parent Collaboration in Elementary Schools - Kusrin, Kusrin; Herzamzam, Dyah Anungrat; Sutisna, Enthis; Yudha, Chrisnaji Banindra (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Changes in educational paradigms and practices after the COVID-19 pandemic are a reflection of educational improvements, examples of good practices, and predictions for the future. This research aims to investigate learning transformation in the post-COVID-19 pandemic era, focusing on the synergy of collaboration between teachers and parents at the elementary school level. The research method used was descriptive qualitative using an elementary school case study method. The research subjects involved teachers and parents of fifth-grade students at the State Elementary School of Wanasari 05 Cibitung Sub-district, who were involved in collaborative efforts. The data collection instruments in this research were interviews and observation. The data obtained would be analyzed using the Miles and Huberman model, with a data analysis process that included data reduction, where the data obtained was compiled, selected, and focused on aspects relevant to the research objectives. The research results demonstrated a transformation in post-pandemic learning approaches, especially through collaboration between teachers and parents. These collaborative practices covered strategies such as regular meetings and utilizing communication technology. It was also found that the synergy between teachers and parents positively impacted the quality of student learning, particularly in terms of motivation, understanding of the material, and social support.